Digital Solutions for Efficient Posyandu Services - Afandi, Muchammad Arif; Azizah, Nuril Lutvi (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract: The advancement of digital technology emphasizes the importance of management information systems in enhancing efficiency in health care. General Background: Integrated Health Posts (Posyandu) are crucial facilities at the village level, focusing on preventive health efforts. Specific Background: In Ganggang Panjang Village, queuing issues and manual data processing hinder Posyandu cadres, leading to inefficiencies. Knowledge Gap: Existing literature lacks tailored solutions for the unique challenges faced by Posyandu in rural areas. Aims: This study aims to design a digital-based Posyandu service system to streamline data collection, recording, and reporting. Results: Using Agile Web Development, the proposed system is browser-accessible, significantly improving operational efficiency through a functional website developed in PHP and JavaScript. Novelty: This research introduces a comprehensive digital solution tailored to rural health providers’ needs. Implications: The findings highlight the potential for digital solutions to enhance health service delivery in rural communities, contributing to improved health outcomes. Highlights: Efficiency Improvement: The digital system streamlines data collection and reporting for Posyandu, reducing manual processing time. Accessibility: The system is designed to be accessible via various browsers, enhancing usability for cadre members. Tailored Solutions: This research addresses the specific challenges faced by rural health providers, promoting effective health service delivery. Keywords: Posyandu, Health Care, Agile Development, Community Health, Information System